Occupational Corporative Order (Relations industrielles / Industrial Relations, 1952)
SummaryThe following text is an English translation by the National Catholic Welfare Conference of the address pronounced in January 31th 1952 by His Holiness Pope Pius XII to the Italian Catholic Association of Employers in which he asked for the Christian spirit as the basis for the social order and criticized forced co-determination.